2015
DOI: 10.1007/s10815-015-0639-3
|View full text |Cite
|
Sign up to set email alerts
|

Agonist depot versus OCP programming of frozen embryo transfer: a retrospective analysis of freeze-all cycles

Abstract: Purpose In segmented ART treatment or so-called 'freeze-all' strategy fresh embryo transfer is deferred, embryos cryopreserved, and the embryo transferred in a subsequent frozen embryo transfer (FET) cycle. The purpose of this cohort study was to compare a GnRHa depot with an oral contraceptive pill (OCP) programming protocol for the scheduling of an artificial cycle FET (AC-FET) after oocyte pick-up (OPU). Methods This retrospective cohort study was conducted on prospectively performed segmented ART cycles pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
(41 reference statements)
3
9
0
1
Order By: Relevance
“…We found that rates of pregnancy and live birth after FET were not affected by OCs used for scheduling endometrial preparation, though it was related to a thinner endometrium. This finding was consistent with another study, which found no effect of OCs used for scheduling FET cycle on pregnancy rate (Ozgur et al, 2016). The underlying mechanism was unclear.…”
Section: Discussionsupporting
confidence: 91%
“…We found that rates of pregnancy and live birth after FET were not affected by OCs used for scheduling endometrial preparation, though it was related to a thinner endometrium. This finding was consistent with another study, which found no effect of OCs used for scheduling FET cycle on pregnancy rate (Ozgur et al, 2016). The underlying mechanism was unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Standard protocols were used for endometrial preparation, with the start of endometrial preparation programmed with the administration of GnRH agonist (≈ 1.88 mg of a 3.75 mg Lucrin Depot®, Abbott Laboratories Ltd., Istanbul, Turkey) or oral contraceptive pill (OCP, Ginera®, 75 μg Gestodene, 30 μg ethinyloestradiol, Bayer, Istanbul, Turkey) [27,28]. Cycles with the shortest time interval between oocyte retrieval and ET (≈ 36 days) were those in which a Lucrin Depot® was administered 7 days after oocyte retrieval and endometrial preparation was started 10 days later with oral estrogen administration [27]. Estrogen (Estrofem, Novo Nordisk, Bagsvaerd, Denmark) was taken orally in a step-up regimen: 2 mg/day from day 1 to 6, 4 mg/day from day 7 to 10, and 8 mg/day from day 11 to 14.…”
Section: Cycle Programming and Endometrial Preparationmentioning
confidence: 99%
“…Embryo cryopreservation technology has undergone significant improvements since its introduction, leading to better outcomes from frozen embryo transfers (FET). The progress seen in embryo cryopreservation has encouraged its routine use in ART centers (Ozgur et al, 2016).…”
Section: Introductionmentioning
confidence: 99%